2013
DOI: 10.1093/jb/mvt011
|View full text |Cite
|
Sign up to set email alerts
|

Na+ conductivity of the Na+-driven flagellar motor complex composed of unplugged wild-type or mutant PomB with PomA

Abstract: PomA and PomB form the stator complex, which functions as a Na(+) channel, in the Na(+)-driven flagellar motor of Vibrio alginolyticus. The plug region of PomB is thought to regulate the Na(+) flow and to suppress massive ion influx through the stator channel. In this study, in order to measure the Na(+) conductivity of the unplugged stator, we over-produced a plug-deleted stator of the Na(+)-driven flagellar motor in Escherichia coli. The over-production of the plug-deleted stator in E. coli cells caused more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 30 publications
4
30
0
Order By: Relevance
“…S1A). We previously showed that overproduction of the plug-deleted PomA/PomB complex inhibits cell growth (19), and this effect was more severely observed in E. coli than in Vibrio cells (34). We also showed that growth inhibition was correlated with the massive influx of sodium ion through the overproduced mutant stators (34); thus, we can evaluate the ion-conducting activity of the stator by this simple assay.…”
Section: Cross-linking Does Not Affect the Stator Assembly Around Thementioning
confidence: 91%
See 1 more Smart Citation
“…S1A). We previously showed that overproduction of the plug-deleted PomA/PomB complex inhibits cell growth (19), and this effect was more severely observed in E. coli than in Vibrio cells (34). We also showed that growth inhibition was correlated with the massive influx of sodium ion through the overproduced mutant stators (34); thus, we can evaluate the ion-conducting activity of the stator by this simple assay.…”
Section: Cross-linking Does Not Affect the Stator Assembly Around Thementioning
confidence: 91%
“…Localization of the stator was observed as described previously (30). Cell growth was monitored as described previously with slight modification (34). Full methods are provided in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…The PomA(R135D) mutation was not suppressed by any fliG mutations examined in this study. PomA(R135D) might cause the defect of ion conductivity previously reported in PomA(R135Q) (22,23). Regarding the pomA fliG double mutations, PomA(H136D) showed an inhibition of motility that was weakly synergistic with some fliG mutations (K284E, R301D, or D309K) ( Table 3; see also Fig.…”
Section: Figmentioning
confidence: 70%
“…In the Na ϩ -driven motor of V. alginolyticus, PomA-H136 was thought to be important for the stator-rotor interaction, because the PomA(H136Y) mutation inhibited the motor function without disrupting the Na ϩ influx through the stators (20,22,23). We introduced charge-reversed mutations into adjacent residues in PomA, R135D, and H136D.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation